ANALISIS WACANA PENCITRAAN PRESIDEN SUSILO BAMBANG YUDHOYONO DALAM BUKU PAK BEYE DAN ISTANANYA - Assiry, Syarifah Sahnath (WACANA, Jurnal Ilmiah Ilmu Komunikasi, 2012)
Along with the times, the need to obtain information for each person is also considered to be very large. So the social life and society, the role of the mass media is very important existence. One of the most stable mass media is the book. Wisnu Nugroho, a Reuters journalist who had served in the National Palace wrote a book Pak Beye and palace. Vishnu started to share stories about the activities inside the palace where since President Sukarnoâs leadershipto Susilo Bambang Yudhoyono, the palace became the country remained in the guard spot sacredness. From a few posts about the activities palace Vishnu, tergambarlah other side of President Susilo Bambang Yudhoyono is notknown by the public. Even in his blog post inviting readers who want to know a lot of events - the incident light that is not important but appealing presented by Vishnu. From this book, readers can see how the other side of President Susilo Bambang Yudhoyono and even this book is considered âdangerousâ by some observers as Vishnu indirectly to dismantle imaging has been done by thePresident. To address this issue, researchers try to address the problem by using descriptive qualitative research. This study was conducted to see how the paper production process, which in this case is done by analyzing news discoursethrough Wisnu Nugroho writings have been published. In this study, researchers used the theory of the construction of political reality and the research method used is a discourse analysis proposed by Teun A. Van Dijk. With this analysis, the study is divided into three levels, namely text, social cognition, and context. Where the core discourse analysis Teun A. Van Dijk is to connect the threedimensions into a single entity. Researchers used a discourse analysis through 8 article condensed imagery in the book Mr. Beye and Istanyanya.With these studies the researchers to conclude that the writings were made by Wisnu Nugroho imaging leads to President Susilo Bambang Yudhoyono, which is regarded as an important element in the life berpolitiknya. From the choice of words and stories accompanied by photographs, Wisnu Nugroho presents writings that are not trying to accuse but provide an opportunity for readers to judge for yourself and share the anxiety he felt for cover in the Palace to the reader.